Examining Claims of Family Process Differences Ensuing From the Choice to Home-School. (January 2015) - Butler, Mark H.; Harper, James M.; Call, Matthew L.; Bird, Mark H.
Advocates of home-schooling claim a variety of positive educational and familial outcomes. Research is needed to examine possible effects of home-schooling on family relationships. We investigated family environment differences between home-schooling and public-schooling families matched in terms of family-centric orientation. Family cohesion was measured using FACES III, and parent–adolescent interaction styles were measured using the Interaction Styles Profile, an instrument formulated for limited research use by the second author based on previous work done with family interaction styles. Mothers, fathers, and adolescent students in 38 public-schooling and 35 home-schooling families completed the measures. The potential confound of preexisting values and commitment to highly cohesive, emotionally connected, cooperative family life in home-schooling families was controlled for by the selection of public-schooling families matched on this variable (family-centric orientation). Family-centric home-schooling families reported statistically significant, but only moderately higher levels of family cohesion and parent–child parallel interaction than family-centric public-schooling families. There were no significant differences between home-schooling and public-schooling families in self-reported symmetrical and complementary interactions. Thus, when controlling for preexisting family-centric orientation, the institution and practice of home-schooling alone appears to produce only moderate (clinically nonrelevant) shifts in family cohesion or positive parallel interaction, suggesting that family-centric families can realize their goals for family cohesion and positive interaction independent of their choice of schooling.